2022
DOI: 10.3390/jcm11185485
|View full text |Cite
|
Sign up to set email alerts
|

High Inferior Vena Cava Diameter with High Left Ventricular End Systolic Diameter as a Risk Factor for Major Adverse Cardiovascular Events, Cardiovascular and Overall Mortality among Chronic Hemodialysis Patients

Abstract: Background: Little is known about the association of inferior vena cava diameter (IVCD) and left ventricular end-systolic diameter (LVESD) with mortality in patients undergoing hemodialysis (HD). Methods: The single medical center observational cohort study enrolled 241 adult chronic HD patients from 1 October 2018 to 31 December 2018. Echocardiography results of IVCD and LVESD prior to dialysis were retrieved and patients were divided into high IVCD and low IVCD groups. Patients who received HD via a tunneled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
1
Order By: Relevance
“…FO by IVC was significantly associated with left atrial enlargement on echocardiography at baseline. Contrary to our findings, Wu et al 22 found that patients with low IVCCI not only had a significantly greater left atrium diameter but also a higher left ventricular end-diastolic diameter, left ventricular end-systolic diameter, and LVMI than those with higher IVCCI. However, IVC ultrasound may be limited by factors that affect IVC diameter or collapsibility, such as respiration, right heart function, and intra-abdominal or intrathoracic pressure changes.…”
Section: Discussioncontrasting
confidence: 99%
“…FO by IVC was significantly associated with left atrial enlargement on echocardiography at baseline. Contrary to our findings, Wu et al 22 found that patients with low IVCCI not only had a significantly greater left atrium diameter but also a higher left ventricular end-diastolic diameter, left ventricular end-systolic diameter, and LVMI than those with higher IVCCI. However, IVC ultrasound may be limited by factors that affect IVC diameter or collapsibility, such as respiration, right heart function, and intra-abdominal or intrathoracic pressure changes.…”
Section: Discussioncontrasting
confidence: 99%